Thor Heyerdahl - voyages of the sun - Trinder, Kingston (Atelier Éditions, 2022)
"Norwegian archaeologist, anthropologist, and explorer Thor Heyerdahl spent decades substantiating unorthodox migration theories through equally unorthodox open-ocean voyages and research expeditions. Afforded unprecedented access to the Kon-Tiki Museum Archive, Thor Heyerdahl: Voyages of the Sun examines the enduring relevance of Heyerdahl's life and his work, the legacy of which is still felt today."
Produced in collaboration with the Kon-Tiki Museum
Keywords: Heyerdahl, Thor -- 1914-2002; Forschungsreise; Heyerdahl, Thor / Travel / Pictorial works; Explorers / Norway / Biography; Anthropologists / Norway / Biography; Voyages and travels / Pictorial works; Kon-Tiki ekspedisjonen / (1947) / Pictorial works; Bildband